Multiwalled Carbon Nanotubes beta-Cyclodextrin Modified Electrode for Electrochemical Determination of Bisphenol S in Water Samples - (:unkn) unknown (PLEIADES PUBLISHING INC, 2019)
A voltammetric sensor for the determination of bisphenol S (BPS) in aqueous samples was fabricated by immobilization of beta-cyclodextrin/multiwalled carbon nanotubes onto the surface of glassy carbon electrode (beta-CD/MWCNTs/GCE). The quantitative determination of BPS was investigated by square wave voltammetry (SWV) and the important analytical characteristics of the beta-CD/MWCNTs/GCE was examined for the detection of bisphenol S. In addition, the predominant experimental factors affecting the voltammetric efficiency were studied. The voltammetric behavior of the beta-CD/MWCNTs electrode in the presence of the BPS was studied, and an irreversible oxidation peak current was obtained at about 0.9 V versus Ag/AgCl. The fabricated electrode exhibited a sufficient linear range from 0.5 to 60 mu M BPS and the limit of detection of the sensor was found to be 0.05 mu M (S/N = 3). Additionally, the applicability of the detailed electrochemical sensor was investigated to determine BPS in tap water and drinking water samples.
Keywords: bisphenol S; voltammetry; cyclodextrin; carbon nanotubes; water analysis; INCLUSION COMPLEX; POLAROGRAPHY